School administrator preparation in Baja California - Charles L. Slater; Elena Esparza; Rosa M. Peña; Carlos Topete; Isaias Alvarez; Trinidad Cerecedo; Jose Maria Garcia (Universidad Autónoma de Madrid, 2015)
This study is an investigation of school administrator preparation in Baja California, México undertaken by professors in the US and Mexico. We used focus groups to determine the day to day challenges of rural school directors and what recommendations might be implied for educational administrator preparation.